Black knight as a strategic choice? Causes and modes of Russia's support to the authoritarianism in Southern Caucasus. (14th May 2019) - Natalizia, Gabriele
Abstract: Despite recurring elections and the transition to multiparty systems, authoritarianism has re-emerged in the Post-Soviet Space. Along with domestic factors, the external dimension should also be considered to fully understand this regional trend. Scholars depict Russia as a typical 'black knight' for democracy. While most of the literature deals with the Kremlin's policies in the 'new' Eastern Europe, this article pays attention to Russia's actions in the relatively understudied Southern Caucasus. Specifically, it investigates why and how Moscow tried to thwart democratization in Armenia, Azerbaijan and Georgia. The diachronic analysis addresses three periods, namely, Yeltsin's presidency, the first Putin presidency and the Putin–Medvedev diarchy. Findings suggest that the Kremlin implemented an increasingly nuanced and intentional black knight strategy in Southern Caucasus, aimed at gaining primacy in the Post-Soviet Space and recognition of its great power status.